2013
DOI: 10.1002/hep.26022
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 3 deficiency leads to interleukin-17-mediated liver ischemia-reperfusion injury

Abstract: Interferon regulatory factor 3 (IRF3) is an important transcription factor in Toll-like receptor 4 (TLR4) signaling, a pathway that is known to play a critical role in liver ischemiareperfusion injury. In order to decipher the involvement of IRF3 in this setting, we first compared the intensity of hepatic lesions in IRF3-deficient versus wildtype mice. We found increased levels of blood transaminases, enhanced liver necrosis, and more pronounced neutrophil infiltrates in IRF3-deficient mice. Neutrophil depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Most likely, IFN regulatory factor 3-dependent events control the IL-23/IL-17 axis in the liver, which is relevant to liver IRI (28). Our own data confirming expression of IL-1b and IL-23 in liver samples from IRI wt mice (data not shown) suggest these cytokines may play a role in driving T cells into IL-17A-releasing effector cells during IRI.…”
Section: Discussionmentioning
confidence: 51%
“…Most likely, IFN regulatory factor 3-dependent events control the IL-23/IL-17 axis in the liver, which is relevant to liver IRI (28). Our own data confirming expression of IL-1b and IL-23 in liver samples from IRI wt mice (data not shown) suggest these cytokines may play a role in driving T cells into IL-17A-releasing effector cells during IRI.…”
Section: Discussionmentioning
confidence: 51%
“…In contrast, minor-to-no increases in IL-17A and IL-23 were measured during reperfusion in wild-type mice subjected to 60 min of 70% hepatic ischemia [8]. Only mice lacking the transcription factor interferon regulatory factor 3 exhibited an increase in IL-17A and IL-23 [8]. This last study therefore ruled out an involvement of IL-17A and IL-23 in hepatic I/R injury.…”
Section: Introductionmentioning
confidence: 76%
“…In addition, Tan et al [7] reported that RORγ + neutrophils drive hepatic I/R injury via an IL-1β/IL-23/IL-17A signaling axis, based on findings in a murine partial hepatic I/R model and plasma samples from 7 patients subjected to hepatic I/R. In contrast, minor-to-no increases in IL-17A and IL-23 were measured during reperfusion in wild-type mice subjected to 60 min of 70% hepatic ischemia [8]. Only mice lacking the transcription factor interferon regulatory factor 3 exhibited an increase in IL-17A and IL-23 [8].…”
Section: Introductionmentioning
confidence: 99%
“…6 Several reports have investigated the roles of IRF1 and IRF3 in liver IRI. 7,8 However, to the best of our knowledge, there are no data supporting the involvement of IRF5 during liver IRI. Therefore, this study was carried out to investigate the role of the TLR4/IRF5 signaling pathway in the hepatic IRI model, by evaluating mRNA expression levels of TLR4/IRF5 axis and its downstream genes, including tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and interleukin 1β (IL-1β).…”
Section: Introductionmentioning
confidence: 90%